The Influence of Quality Management and Market Orientation on Small and Medium-sized Enterprises (SMEs) Performance in Indonesia through the Enterprise Risk Management (ERM) - Meinar Sirait, Evita (Dinasti International Journal of Digital Business Management, 2023)
Literature Article Review on Enterprise Risk Management, Quality Management and Market Orientation on SMEs performance is a scientific article that aims to build a research hypothesis on the influence of inter-variables to be used in further research, within the scope of Risk and Strategic Management. The method of writing this Literature Review article is the library research method, which is sourced from online media such as ProQuest, Google Scholar, and other academic online media The results of this article are that: 1) Quality Management affects SMEs performance, 2) Market Orientation affects SMEs performance and 3) Enterprise Risk Management (ERM) affects SMEs performance.